Kajian Kriminologis Keterlibatan Wanita dalam Tindak Pidana Narkotika - Riska Fahrani Rais; Julianus Edwin Latupeirissa; Iqbal Taufik (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study examines the criminological aspects of women's involvement in narcotics crimes. The increasing circulation and abuse of narcotics in Indonesia has become a serious social and legal problem, with women increasingly found to be involved in such criminal activities. This research aims to analyze the forms of women's involvement in narcotics crimes, the factors that cause such involvement, and the efforts that can be undertaken to address this issue. The research uses a normative juridical method, focusing on the analysis of legal norms, legislation, and relevant literature related to narcotics crimes. The study employs statutory, conceptual, and case approaches, with legal materials systematically analyzed through qualitative descriptive analysis, legal interpretation, and comparative legal reasoning to examine provisions and criminological perspectives regarding women's participation in narcotics-related offenses. The findings indicate that women's involvement in narcotics crimes is influenced by various interconnected factors, including economic pressure, social environment, low educational background, and psychological factors such as curiosity and social influence. In many cases, women are also exploited by organized criminal networks and used as couriers because they are considered less suspicious by law enforcement authorities. Therefore, effective countermeasures require comprehensive strategies that combine preventive and repressive approaches, including stronger law enforcement, improved public awareness, and social and economic empowerment programs for women to reduce their vulnerability to involvement in narcotics crimes.